Functional activity, functional connectivity and complex network biomarkers of progressive hyposmia Parkinson’s disease with no cognitive impairment: evidences from resting-state fMRI study - Geng, Lei; Cao, Wenfei; Zuo, Juan; Yan, Hongjie; Wan, Jinxin; Sun, Yi; Wang, Nizhuan (Frontiers in Aging Neuroscience, 2024)
Background: Olfactory dysfunction stands as one of the most prevalent non-motor symptoms in the initial stage of Parkinson's disease (PD). Nevertheless, the intricate mechanisms underlying olfactory deficits in Parkinson's disease still remain elusive. Methods: This study collected rs-fMRI data from 30 PD patients (15 with severe hyposmia (PD-SH) and 15 with no/mild hyposmia (PD-N/MH)) and 15 healthy controls (HC). To investigate functional segregation, the amplitude of low-frequency fluctuation (ALFF) and regional homogeneity (ReHo) were utilized. Functional connectivity (FC) analysis was performed to explore the functional integration across diverse brain regions. Additionally, the graph theory-based network analysis was employed to assess functional networks in PD patients. Furthermore, Pearson correlation analysis was conducted to delve deeper into the relationship between the severity of olfactory dysfunction and various functional metrics; Results: We discovered pronounced variations in ALFF, ReHo, FC, and topological brain network attributes across the three groups, with several of these disparities exhibiting a correlation with olfactory scores. Conclusion: Using fMRI, our study analyzed brain function in PD-SH, PD-N/MH, and HC groups, revealing impaired segregation and integration in PD-SH and PD-N/MH. We hypothesize that changes in temporal, frontal, occipital, and cerebellar activities, along with aberrant cerebelluminsula connectivity and node degree and betweenness disparities, may be linked to olfactory dysfunction in PD patients.